Strategic Decision Analysis for Capacity Expansion with Migration for Semiconductor Assembly Industry - J Chen, Yenming (IJRDO - Journal of Applied Management Science, 2017)
This paper aims to understand strategic decision-making for capacity expansionvia the use of the analytic network process, and to investigate further the difference inpolicies for capacity expansion in a situation of capacity migration. As the government’swestward policy slackens, and industries strive for business growth, higher profitscompetency, they have moved their products and capacity to China as they realize the largerlabor population, lower production cost, easier land access and additional premium policiesthere, a phenomenon termed capacity migration. This study focuses on how semiconductorassembly industries make capacity expansion strategies while facing capacity migration. Asmost strategic analysis methods cannot provide actual manipulation methods, this researchaims to build a multi-principle strategy model that can provide operable methods for abstractdecisions. Findings of this study reveal that in the industrial environment where there iscapacity migration, the semiconductor assembly industry should considers the PreemptionStrategy when making capacity expansion strategic decisions.